Identity of Siberian Cities and Public Spaces. ZES 14 Discussion Club. 27–28 June, Krasnoyarsk - Marina Tkacheva (Proekt Bajkal, 2014)
The article presents a record of a round-table discussion held as part of the Festival “Zodchestvo of Eastern Siberia 2014”. The problem of identity of Siberian cities was discussed by the leading architects of Russia, urban specialists, historians, ethngraphers, cultural specialists, etc. Different debatable opinions on the past, present and future of Siberian cities were advanced during the discussion.